MEASURING AWARENESS ABOUT MUTUAL FUNDS: A STUDY ON BANK EMPLOYEES IN TRIPURA - Deb, Sujit; Singh, Ranjit; Pandey, Lata kumari; Yadav, Vibha; Deb, Sankha Subhra (International Journal of Accounting & Finance Review, 2023)
This paper aims to find out bank employees' awareness level towards mutual funds and their impact on investment in the mutual fund. The study was conducted using a simple random sampling design of 262 employees working in different banks in Tripura, India. The size of the population was 815 employees. The data was collected using a structured questionnaire. Ordinal logistic regression analysis and chi-square test were used to assess the impact of employees' awareness on investment in mutual funds. It was found that the overall level of awareness of bank employees in Tripura towards mutual funds was high, and the level of awareness and volume of investment in the mutual fund are directly related. We conducted a preliminary evaluation study on the awareness level of mutual funds of bank employees using ten multiple questions having one option correct. This study will provide a complete informative summary to the policymaker, bank employees, and non-bank employees to make decisions for investment. It will help to take all necessary steps to spread updated awareness about mutual funds among investors. The study consists of several vital inputs which will be useful to the academician to go for further study in detail. Further research may be done in this field by taking another variable factor that needs to be considered to measure the employees' awareness level.JEL Classification Codes: G11, G14, G24, G38, N25.